Dynamic Macroeconomic Linkages in Indonesia Using Wavelet Transform Coherence Analysis - Nabila Putri Anindya; Aisyah Nur Zahra; Nurul Azizah Safitri; Andika Bagas Wicaksono; Fajar Maulana Hidayat (Journal of Economics Business Industry, 2025)
This study aims to analyse the dynamic relationships among six key macroeconomic variables in Indonesia, namely Gross Domestic Product (GDP), the BI 7-Day Reverse Repo Rate (BI Rate), the Jakarta Composite Index (JCI), the Consumer Price Index (CPI), the Open Unemployment Rate (OUR), and global crude oil prices represented by West Texas Intermediate (WTI), over the period from 2010 to 2024. The study employs descriptive statistical analysis, Pearson correlation analysis, and the Wavelet Transform Coherence (WTC) method to assess how the relationships among these variables evolve across time and frequency domains. The results indicate that CPI is the most stable variable, while WTI and JCI exhibit substantially higher volatility, particularly during the COVID-19 pandemic and the 2013 to 2015 global oil price collapse. A strong positive relationship is observed between CPI and the BI Rate, consistent with the Taylor Rule framework, while strong coherence between CPI and WTI during during periods of global commodity price fluctuations reflects Indonesia’s sensitivity to global energy price movements. However, several findings reveal structural complexities within the Indonesian economy, including an unexpectedly weak or positive relationship between GDP and unemployment, potentially associated with the dominance of the informal sector and uneven labour absorption across industries. In addition, the relatively weak static CPI–WTI correlation suggests that domestic fuel subsidy policies partially shield consumer prices from external oil price shocks. These findings provide important implications for policymakers in designing responsive monetary and fiscal strategies, for investors managing portfolio exposure to commodity cycles, and for researchers seeking to deepen understanding of macroeconomic dynamics in emerging market economie